Rekrutmen Tenaga Kerja (Pegawai) sebagai Pilar Penguatan Sumber Daya Manusia dalam Pendidikan Islam - Saputra, Remon; Maryani, Maryani; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Recruitment practices in various Islamic educational institutions still face a number of challenges. This study aims to analyze the concept, principles, and implementation of employee recruitment in Islamic educational institutions from the perspective of human resource management based on Islamic values. This study uses a qualitative descriptive approach through a literature review, drawing data from journals published by google scholar, researchgate, garuda, and sinta, published between 2020-2025, related to Islamic education management. Data collection was conducted throught documentation, and data analysis was conducted using content analysis. The findings indicate that an ideal recruitment process in Islamic education must adhere to the principles of amanah (trustworthiness), justice, professionalism, transparency, and anti-nepotism, as emphasized in QS. Al-Qashash verse 26. The desired employee criteria include professional competence, Islamic personality, spirituality, and social skills. The implementation in various Islamic educational institutions shows that although these Islamic recruitment principles have been applied, challenges remain—such as limited resources, lack of standardized procedures, and minimal utilization of digital technology in the selection process